Os processos de gestão escolar e suas interações com a comunidade de Nova Boa Vista: interrelações espaços e escola - Thums, Angela (Universidade do Vale do Rio dos Sinos, 2020)
The theme of this thesis is within the field of school management.Theobject of investigation is the interaction of school management with the city, the community,and the residents.The main focus of the thesis is to understand the experiences and practices of school management within the municipal and state school system which stem from the dynamics and interactions established with the communities of Nova Boa Vista/RS.The method chosenfor theanalyses is the ethnography.The strategies for datacollectionused were:non-directed interviews, informal visits, observation of participants, photographic record, and document analysis, with emphasis on campus diary.The empirical field for the research is comprised of thecity, the interiorcommunities, the residents and the two schools in the municipality of Nova Boa Vista/RS.The resultsappear as a spiral, aggregating results from the city, the interior communities, the residents, as well asestablishing connections with the context of the schools.In the macro context, it is possible to identify the new social relationships that people establish with work, the adaptability and flexibility of the workday; the linkage with property; new business relationships through partnerships and collaboration, outsourcing of work and the nucleation of schools.In the micro context, it is possible to determine how the organizational culture of the schools is strengthened as well as the impact the displacement of children from the interior to the city has on communities which, in turn, become weaker. One can also define the bonds that people develop with the community and the school. In addition, it was also observed that the community establishes and nurtures strong links with the historical context of German immigration and colonization. Therefore, the school management in the stateand municipal educational system takes on a style of participation and collaboration. Decisions are interconnected with the lives, memories, and practices of the community. The schools are built collectively by the residents within the cultural and socialcontext according to their individual experiences and practices which, in turn, are linked to the cultural and historical context of the community. As a result, establishes not only a spirit of cooperation and volunteerism but also a sense of belonging tothe place and the community.
Keywords: Gestão escolar; Etnografia; Comunidade; Imigração; Cultura; School management; Ethnography; Community; Immigration; Culture; ACCNPQ::Ciências Humanas::Educação